The Gemini Deep Deep Survey: II. Metals in Star-Forming Galaxies at Redshift 1.3 - Savaglio, S; Glazebrook, K; Abraham, R; Crampton, D; Chen, H; McCarthy, P; Jorgensen, I; Roth, K; Hook, I; Marzke, R; Murowinski, R; Carlberg, R (Institute of Physics Publishing, 2003)
The goal of the Gemini Deep Deep Survey (GDDS) is to study an unbiased sample of K<20.6 galaxies in the redshift range 0.8<z<2.0. (ism)="" -19.65.="" 1.34<z<1.97="" 13="" 38%="" <="" a="" absolute="" and="" contains="" determine="" element="" enrichment="" fields="" first="" galaxies="" heavy="" here="" identified="" in="" interstellar="" m_2000="" magnitude="" medium="" number="" of="" properties="" sample="" statistical="" subsample="" survey="" the="" total="" two="" uv="" we="" with="" z="">1.3. The selected objects have colors typical of irregular and Sbc galaxies. Strong [OII] emission indicates high star formation activity in the HII regions (SFR~13-106 M_sun/yr). The high S/N composite spectrum shows strong ISM MgII and FeII absorption, together with weak MnII and MgI lines. The FeII column density, derived using the curve of growth analysis, is logN_FeII = 15.54^{+0.23}_{-0.13}. This is considerably larger than typical values found in damped Ly-alpha systems (DLAs) along QSO sight lines, where only 10 out of 87 (~11%) have logN_FeII > 15.2. High FeII column densities are observed in the z=2.72 Lyman break galaxy cB58 (logN_FeII ~ 15.25) and in gamma-ray burst host galaxies (logN_FeII ~ 14.8-15.9). Given our measured FeII column density and assuming a moderate iron dust depletion (delta_Fe ~ 1 dex), we derive an optical dust extinction A_V ~ 0.6. If the HI column density is log N(HI)<21.7 (as in 98% of DLAs), then the mean metallicity is Z/Z_sun > 0.2. The high completeness of the GDDS sample implies that these results are typical of star-forming galaxies in the 1</z<2.0.>